2021
DOI: 10.3389/fpsyt.2021.729104
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in Persons With Hidradenitis Suppurativa: Factors Associated With Sexual Desire and Functioning Impairment

Abstract: Hidradenitis Suppurativa (HS) is a chronic skin disease involving intimate and sensitive areas and affecting physical and mental health. We investigated the prevalence of sexual desire and functioning impairment, and their associations with quality of life, anxiety, depression, minor psychiatric disorders (MPD), and clinical features (e.g., disease severity) in 77 patients with HS who completed self-report measures and answered to questions assessing socio-demographic characteristics, lifestyle habits, and hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Sampogna et al, analyzing the impact on sexual life through question 9 of the DLQI in 3485 dermatological patients, observed that HS was the skin condition associated with the greater sexual impairment [ 130 ]. Indeed, several studies reported (i) a high incidence of sexual impairment in HS patients [ 131 , 132 , 133 ], (ii) significantly greater sexual dysfunction (meaning impairment in the physical sphere) [ 134 , 135 , 136 ] and (iii) sexual distress (meaning impairment in the psychological sphere) [ 134 , 135 , 137 ] in patients affected by HS in comparison to control subjects ( Figure 2 ). Interestingly, the evidence from available studies indicates that the disease impact on sexual functioning might vary depending on gender.…”
Section: Hs and Sexual Impairmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Sampogna et al, analyzing the impact on sexual life through question 9 of the DLQI in 3485 dermatological patients, observed that HS was the skin condition associated with the greater sexual impairment [ 130 ]. Indeed, several studies reported (i) a high incidence of sexual impairment in HS patients [ 131 , 132 , 133 ], (ii) significantly greater sexual dysfunction (meaning impairment in the physical sphere) [ 134 , 135 , 136 ] and (iii) sexual distress (meaning impairment in the psychological sphere) [ 134 , 135 , 137 ] in patients affected by HS in comparison to control subjects ( Figure 2 ). Interestingly, the evidence from available studies indicates that the disease impact on sexual functioning might vary depending on gender.…”
Section: Hs and Sexual Impairmentmentioning
confidence: 99%
“…The association between impaired sexuality and disease severity is controversial. To date, the evidence does not support a correlation between disease severity and a higher risk of sexual distress or dysfunction [ 131 , 132 , 134 , 135 , 140 ]. Interestingly, while HS was not found to be associated with increased sexual impairment in previous research [ 132 ], in their cross-sectional study, Cuenca-Barrales et al observed that the presence of a stable partner was a protective factor against sexual distress in women [ 137 , 140 ].…”
Section: Hs and Sexual Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Its clinical heterogeneity makes every taxonomic effort extremely difficult highlighting that clinically similar phenotypes do not necessarily belong to the same genotype. 2 . Beyond the physical aspect, HS also deeply impairs the quality of life from social interaction to the sexual quality of life, 2 which in turn could potentially increase binge eating, alcoholism and opioid abuse.…”
Section: Introductionmentioning
confidence: 99%